Judging the Quality of Legal Research: A Qualified Response to the Demand for Greater Methodological Rigour - Theunis Roux (Legal Education Review)
Capstone programs are increasing recognised as high-impact value-laden learning experiences for students, especially in aiding the transition of final year students to professional practice. Although these learning programs have a long history in many disciplines, they are a very recent inclusion in law curriculum in Australia. This paper reports on a project designed to renew the final year law curriculum in Australia by developing a principled approach to designing capstone programs. This framework is based on six key principles, which are transition, integration and closure, diversity, engagement, assessment, and evaluation. The project also identified two themes underpinning capstone experiences which sit behind the six principles - integration and closure, and transition. The principled approach advocated by the authors’ bridges the gap between curriculum theorising and practice. This paper discusses the theme of transition and how the resources provided in the project Toolkit assist unit coordinators to design effective final year capstone programs. The toolkit outlines the six principles, providing commentary on each, and also offers suggestions for subject models along with examples of actual capstone programs, all of which have been designed to facilitate smooth transitions for final year students as they move from undergraduate to emerging professional.